Geraniin Protects High-Fat Diet-Induced Oxidative Stress in Sprague Dawley Rats - Chung, Alexis Panny Y. S.; Gurtu, Sunil; Chakravarthi, Srikumar; Moorthy, Mohanambal; Palanisamy, Uma D. (Frontiers in Nutrition, 2018)
Geraniin, a hydrolysable polyphenol derived from Nephelium lappaceum L. fruit rind, has been shown to possess significant antioxidant activity in vitro and recently been recognised for its therapeutic potential in metabolic syndrome. This study investigated its antioxidative strength and protective effects on organs in high-fat diet-induced (HFD) rodents. Rats were fed HFD for six weeks to induce obesity, followed by 10 mg/kg and 50 mg/kg of geraniin supplementation for four weeks to assess its protective potential. The control groups were maintained on standard rat chows and HFD for the same period. At the 10th week, oxidative status was assessed and the pancreas, liver, heart and aorta, kidney and brain of the Sprague Dawley (SD) rats were harvested and subjected to pathological studies. HFD rats demonstrated changes in redox balance; increased protein carbonyl content, decreased levels of superoxide dismutase, glutathione peroxidase and glutathione reductase with a reduction in the non-enzymatic antioxidant mechanisms and total antioxidant capacity, indicating a higher oxidative stress index. In addition, HFD rats demonstrated significant diet-induced changes particularly in the pancreas. Four-week oral geraniin supplementation, restored the oxidative stress observed in the HFD rats. It was able to restore oxidative stress biomarkers, serum antioxidants and the glutathione redox balance (GSH/GSSG ratio) to levels comparable to that of the control group, particularly at dosage of 50 mg geraniin. Geraniin was not toxic to the HFD rats but exhibited protection against glucotoxicity and lipotoxicity particularly in the pancreas of the obese rodents. It is suggested that geraniin has the pharmaceutical potential to be developed as a supplement to primary drugs in the treatment of obesity and its pathophysiological sequels.